Analisis Pembatasan Kewenangan Bawaslu dalam Sentra Gakkumdu Perspektif Sosiologi Fungsionalis - Widowati, Diyah Nur; Miranda Inko Sherly (Tumoutou Social Science Journal, 2025)
The enforcement of election crimes committed by Bawaslu is the reality that occurs that not always elections can run directly, freely, confidentially, honestly, and fairly. Based on the analysis of conditions that are mainly studied through the reality that occurs, the obstacles that often occur are differences in perception between members of the Gakkumdu Center, loss of evidence of conjecture, limited time, and limited Bawaslu human resources. Through Law No. 22 of 2007, the existence of Bawaslu is no longer subordinate to the KPU. The above conditions then initiated the birth of development research in the framework of claiming novelty, parsing the role of each institution in the Gakkumdu Center through a new point of view, namely functionalist sociology. The function of Sentra Gakkumdu is as a coordination forum in the process of handling every violation of election crimes, implementation of the election criminal pattern itself, data centers, competency improvement, evaluation monitoring. Therefore, it is necessary to coordinate and collaborate to build between law enforcement members in the Gakkumdu Center.